THE IMPORTANCE OF EXCISES FOR THE FISCAL BALANCE IN THE REPUBLIC OF SERBIA - Kalaš, Branimir (Journal of process management and new technologies, 2021)
Excises are one of the most generous taxes in the Republic of Serbia and this tax form should be determined at adequately level in order to provide positive effect on the economy. The aim of this paper is to investigate the relationship between excises and fiscal balance in the Republic of Serbia for the period 2008-2019. Empirical research includes descriptive statistics, VAR model and Granger causality test in order to determine their relationship. Results of the paper show that excises have significant and positive effect on fiscal balance and there is unidirectional causality from excises to fiscal balance in the analyzed period.